Congenital Heart Defects in Hirschsprung's Disease: A Survey in Iranian Population - Minoo Fallahi; Fariba Alaei; Mohammad Reza Khalilian; Mastaneh Alaei; Kourosh Vahidshahi; Faezeh Ansari; Yalda Nilipour (Mashhad University of Medical Sciences, 2022)
Background: Hirschsprung's disease (HSCR) may be accompanied by other anomalies, including congenital heart disease (CHD), resulting in additional complications. This study was performed to evaluate the prevalence and type of concomitant CHD in hospitalized children with HSCR. Methods: All HSCR patients (n=129) admitted to Mofid Children's Hospital in Tehran, Iran, from April 2016 to August 2019 were investigated in a descriptive cross-sectional study. Two-dimensional, M-mode and pulsed, continuous, and color Doppler provided echocardiography were applied to evaluate cardiac structure and function. Results: CHD was observed in 48 (37.2%) cases, and the most common anomalies were Atrial Septal Defect (ASD) in 20 (15.5%), Ventricular Septal Defect (VSD) in 1 (0.8%), Patent Ductus Arteriosus (PDA) in 2 (1.6%), Tetralogy of Fallot in 3 (2.3%), ASD and Pulmonary stenosis in 2 (1.6%), ASD and PDA in 7 (5.4%), ASD and VSD in 3 (2.3%), as well as VSD and PDA in 2 (1.6%) patients. Conclusion: Cardiac anomalies are relatively prevalent in the Iranian HSCR population participating in the present study. In addition, early echocardiographic evaluation in the setting of HSCR is recommended.